The Status of Blueberry Gall Midge in the Southeastern United States - Oscar Liburd; Erin Finn (EDIS, 2002)
This document is ENY-825, one of a series of the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: September 2002.